Noisy Galvanic Vestibular Stimulation Sustainably Improves Posture in Bilateral Vestibulopathy - Fujimoto, Chisato; Egami, Naoya; Kawahara, Takuya; Uemura, Yukari; Yamamoto, Yoshiharu; Yamasoba, Tatsuya; Iwasaki, Shinichi (Frontiers in Neurology, 2018)
Patients with bilateral vestibulopathy (BV) suffer from persistent postural imbalance, leading to a marked decrease in quality of life and a higher risk of falls. However, so far, the effective treatments for BV are very limited. We examined whether long-term noisy galvanic vestibular stimulation (nGVS) keeps improving body balance after the cessation of the stimulus in BV patients. Thirteen BV patients received nGVS for 30 min with a lower intensity than the intensity at which they feel any cutaneous sensations, and their postural movement was monitored for 6 h after the stimuli. The same session was repeated at 14-day intervals. Stance tasks on two legs were performed with eyes closed. The velocity of the center of pressure (COP) movement, the area enclosed by the COP movement, and the root mean square of the displacement of the COP were measured. The power spectrum of the COP movement was assessed. Subjective improvement of body balance was graded as worsened (–2), slightly worsened (–1), unchanged (0), slightly improved (+1) and improved (+2) in comparison with that without nGVS. In each session, the velocity of the COP movement was significantly improved for 6 h after the stimulus had ceased (P < 0.01). Concomitantly, the mean frequency of the COP power spectrum was significantly reduced in the anterior-posterior axis (P < 0.05). Subjective symptoms of imbalance were improved during the post-stimulation effect (P < 0.05). nGVS leads to an improvement in body balance that lasts for several hours after the end of the stimulus in BV patients with a reduction in the high-frequency components of their postural movement.